Cross-sectional mixed-methods study protocol exploring the enablers and barriers for people with severe and enduring mental illness in Jamaica when accessing healthcare for chronic physical illness. Issue 8 (4th August 2020) - Whitehorne-Smith, Patrice; Burns, Sharyn; Milbourn, Ben; Abel, Wendel; Martin, Robyn
Abstract : Introduction: Extant international research suggests that people with severe and enduring mental illness (PWSEMI) experience increased rates of chronic physical illness (CPI), reduced life expectancy and higher mortality than those in the general population. The high prevalence of CPI among PWSEMI is associated with a number of barriers that this population experiences when accessing physical healthcare. Although substantial research has been conducted in North America, Europe and Australia, there appears to be a paucity of research exploring CPI among PWSEMI in the Caribbean region, although this region has reported very high rates of non-communicable diseases within its populations. The current study will be situated in Jamaica and will explore the enablers and barriers to PWSEMI accessing healthcare for CPI. Methods and analysis: A convergent mixed-method design will explore the enablers and barriers to accessing healthcare for CPI among PWSEMI. This cross-sectional study will collect data from PWSEMI, caregivers and family members, community health aides, primary care physicians, psychiatrists and health policymakers. Ethics and dissemination: The study findings will provide baseline data describing the prevalence of CPI among PWSEMI in Jamaica and will identify enablers for, and barriers to, PWSEMI accessing CPI care. Findings will be disseminated widely in Jamaica and internationally to key stakeholders through publications and conferences. Institutional ethical approval was granted from Jamaica's Ministry of Health and Wellness Medico-legal Ethics Review Panel (# 2019/49), the Curtin University Human Research and Ethics Committee (HRE 2020–0022) and the University of the West Indies FMS Ethics Committee (ECP 101, 19/20).